Folksy space: the right to belong in the cityscape - Tuneld, Sara (My University, 2021)
Architectural projects are often framed with an aim to create inclusive spaces, but creating such spaces is complex since visions also work excluding. The role of the architect is therefore dualistic in its nature since the profession holds the capacity to imagine a better world but doing so is to practice an elitist agency since this also always will exclude someone from this vision. Thus, there is a need to acknowledge and be transparent about who we work with matters of inclusion in practice. The purpose of the thesis is to analyze how matters of inclusion are handled within a contemporary architectural project and to develop a theoretical tool that can be used to discuss and raise awareness of matters of inclusion and exclusion in architectural debate. The thesis seeks to answer the research questions if an inclusive architectural strategy risks becoming excluding in its target group and in the continuation how we deeper can understand and discuss the duality of our architectural role. Social theory provides an important foundation for answering these questions, where literature studies have been the main method for creating a framework to explain the factors that set the prerequisites for inclusiveness and exclusiveness in the cityscape.To contextualize the research, a case study of the Oslo Opera House was carried out to analyze how inclusion becomes a contemporary architectural strategy, where folksiness is found as often used as a term for this ambition. The study shows how this type of planning has been used throughout the project, and how well the current situation responds to these set expectations. The framework shows that the probability that a person resides in space is dependent on a complex mix of factors such as power structures and social capital. Thus, inclusive planning as a strategy also comes with a risk and should therefore be evaluated transparently. In order to understand and discuss these matters and reach the dualist relation between elitism and folksiness, the result of the research is a theoretical tool that can be used to frame this notion.
Keywords: folksiness, elitism, inclusion, the right to the city, Oslo opera house